Lack of ApoA-I in ApoEKO Mice Causes Skin Xanthomas, Worsening of Inflammation, and Increased Coronary Atherosclerosis in the Absence of Hyperlipidemia. Issue 7 (19th May 2022) - Busnelli, Marco; Manzini, Stefano; Colombo, Alice; Franchi, Elsa; Bonacina, Fabrizia; Chiara, Matteo; Arnaboldi, Francesca; Donetti, Elena; Ambrogi, Federico; Oleari, Roberto; Lettieri, Antonella; Horner, David; et al.
Abstract : Background: HDL (high-density lipoprotein) and its major protein component, apoA-I (apolipoprotein A-I), play a unique role in cholesterol homeostasis and immunity. ApoA-I deficiency in hyperlipidemic, atheroprone mice was shown to drive cholesterol accumulation and inflammatory cell activation/proliferation. The present study was aimed at investigating the impact of apoA-I deficiency on lipid deposition and local/systemic inflammation in normolipidemic conditions. Methods: ApoE deficient mice, apoE/apoA-I double deficient (DKO) mice, DKO mice overexpressing human apoA-I, and C57Bl/6J control mice were fed normal laboratory diet until 30 weeks of age. Plasma lipids were quantified, atherosclerosis development at the aortic sinus and coronary arteries was measured, skin ultrastructure was evaluated by electron microscopy. Blood and lymphoid organs were characterized through histological, immunocytofluorimetric, and whole transcriptome analyses. Results: DKO were characterized by almost complete HDL deficiency and by plasma total cholesterol levels comparable to control mice. Only DKO showed xanthoma formation and severe inflammation in the skin-draining lymph nodes, whose transcriptome analysis revealed a dramatic impairment in energy metabolism and fatty acid oxidation pathways. An increased presence of CD4 + T effector memory cells was detected in blood, spleen, and skin-draining lymph nodes of DKO. A worsening of atherosclerosis at the aortic sinus and coronary arteries was also observed in DKO versus apoE deficient. Human apoA-I overexpression in the DKO background was able to rescue the skin phenotype and halt atherosclerosis development. Conclusions: HDL deficiency, in the absence of hyperlipidemia, is associated with severe alterations of skin morphology, aortic and coronary atherosclerosis, local and systemic inflammation.